Le tropisme philosophique de Milan Kundera : Le roman à la recherche de la définition perdue - Wan, Jin (Labyrinth, 2020)
The Philosophical Tropism of Milan Kundera: The Novel in Search of the lost Definition The philosophical tropism of Milan Kundera is manifested in particular by his novels in search of lost definition. The creation and the redefinition of concepts in his novels aiming at elucidating the essence show his ambition to " make philosophy in the way of a novelist". We examine his processes in the invention of concepts and the definition of words, as well as the similarity between his works and phenomenology, particularly Merleau-Ponty's approach. Through the metaphoricity of language and the inseparability between definitions and characters in his novels, Kundera revives a missed rendezvous between philosophy and novel. The definition of concept is no longer the privilege of philosopher. By the tireless pursuit of defining "the indefinable", Kundera transforms the novel into a place of phenomenological description and a field of thought experimentation, despite his ambiguity about this rapprochement.